2011
DOI: 10.1055/s-0031-1275168
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Management of Sternal Wound Infection

Abstract: Sternal wound infection is a life-threatening complication after cardiac surgery associated with high morbidity and mortality. Past treatment options have included closed suction and continuous irrigation. Current paradigms in the management of sternal wound infection include surgical debridement, vacuum-assisted closure therapy, flap coverage, and sternal plating. We provide a general overview of sternal wound infection and treatment options for the plastic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 65 publications
1
123
0
2
Order By: Relevance
“…Tracheostomy prior to any identified SWI occurred in 411 patients (2.2%), and the median [IQR] time from post-surgical ICU admission to tracheostomy was 14 [10][11][12][13][14][15][16][17][18][19] Table 2. Tracheostomy was an independent predictor of SWI (adjusted OR 2.8; 95% CI 1.9 to 4.2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracheostomy prior to any identified SWI occurred in 411 patients (2.2%), and the median [IQR] time from post-surgical ICU admission to tracheostomy was 14 [10][11][12][13][14][15][16][17][18][19] Table 2. Tracheostomy was an independent predictor of SWI (adjusted OR 2.8; 95% CI 1.9 to 4.2).…”
Section: Resultsmentioning
confidence: 99%
“…16 As a result, many clinicians are concerned about proceeding with tracheostomy, as direct soiling of the healing sternal wound could result. Tracheostomy in critically ill patients does not lend itself easily to a randomized interventional trial.…”
Section: Discussionmentioning
confidence: 99%
“…Wound infection is life-threatening complication associated with an increased risk of short and long term morbidity and mortality in patient undergoing (CABG) surgery [4,5]. According to the Nork-Marash Medical Center (NMMC), the new cases of wound infection are 7.4% in patients after CABG, a further study found to be range from 1-10% [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Pre and intra-operative predictors are significantly associated withthe increase risk of wound infection. Although in the advance revolution of cardiac surgery the optimization/development of sternal wound infectionsisless decreased [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its widespread utility, this incision is not free of complications, which include infected median sternotomy wounds (IMSWs) that can progress to mediastinitis with potentially fatal consequences. The incidence of post-sternotomy mediastinitis ranges from 1 to 5 % with a mortality rate of 10-47 % [2].…”
mentioning
confidence: 99%